The Role of Educational Program Evaluation in Improving the Quality of Learning - Desi Devita Sari; Rusdiana Navlia (Penerbit Presisi Pustaka, 2026)
This study aims to examine the role of educational program evaluation in improving the quality of learning. Educational program evaluation is a systematic and planned process for collecting information, conducting analysis, and assessing the success of an educational program in achieving its stated objectives. Evaluation aims to provide input, improve accountability, and support curriculum development. The method used in this study is library research, where data is obtained by gathering information from various sources such as books, journals, and relevant research. It was found that evaluation serves as a measuring tool to gauge the effectiveness of the teaching and learning process, providing constructive feedback for students and educational staff, and encouraging the development of curriculum and educational policies. Through evaluation, educators can determine how well students understand the material taught and the extent to which learning objectives are achieved.